Parenting Self-Efficacy Among Working Mothers in Central Sulawesi - Hesti Putri Setianingsih; Sita Awalunisah; Zakiyyatul Imamah (Indonesian Journal of Early Childhood Education Studies, 2024)
Mothers have a crucial role in household affairs and childcare in the family. But now, the role of mothers is starting to change. Some mothers choose to work for various reasons including being able to meet needs, self-actualization, knowledge experience, and to fill spare time. Working mothers will easily experience stress, fatigue, or even frustration if they cannot balance between work and their responsibilities as housewives. This condition will have a bad impact on the family. Parenting self-efficacy is a parent's confidence in their competence in caring for and providing care for children that positively influences the child's behavior and development. Therefore, the purpose of this study is to describe the role of parenting self-efficacy. Participants consisted of 192 working mothers who had children between the ages of 0 and 8. This study used a random sample. Working mothers were given a questionnaire that was distributed according to the SEPTI scale to measure their self-efficacy in parenting. The results showed a significant relationship between stress and well-being among working mothers, t-count values of t = 129,872 > t-table 1,994. The higher the stress level of the mothers, the lower the self-effectiveness of their parents. Conversely, the lower the mother's stress level, the higher their parents' self-efficiency. In the end, the hypothesis was accepted.